Oral candidal carriage and its association with dental carious lesions in asymptomatic adults: a cross-sectional study from the UAE - Suhail H. Al-Amad; Betul Rahman; Nadia Khalifa; Manal A. Awad (BMC, 2021)
Abstract Background Candida's potential association with dental caries has previously been reported in children. This research aimed at investigating the associations between Candida species in whole saliva and dental and periodontal health indices in a sample of adult patients. Methods A cross-sectional study involving 160 patients investigated the associations between Candida species collected by oral rinse technique, and Decayed, Missing, and Filled Surfaces (DMFS), and periodontal health indices. Chi-square and Independent Samples t-test were used to assess the associations between Candida carriage and confounding variables. Binary logistic regression was used to assess association strengths between Candida carriage and DMFS, adjusted for socio-demographic variables, diabetes mellitus and plaque index. Results Candida colonies were identified in 49 (30.6%) patients with CFUs ranging from 103 to 105 colonies per mL. The quantity of Candida CFUs increased with age (r = 0.200; p < 0.05). Among all dental and periodontal health indices, only DMFS was significantly associated with higher values of Candida carriage (p = 0.034), and this association was independent from sex, age, smoking, diabetes mellitus and plaque index (OR: 1.014; 95% CI 1.0-1.03; p = 0.048). Conclusion The association between Candida species in whole saliva and DMFS reported here supports an etiological role of Candida in dental cariogenesis among adults.